PENGARUH TINGKAT PENGETAHUAN DENGAN IMPLEMENTASI PROGRAM DAGUSIBU OBAT ANTIBIOTIK PADA MASYARAKAT DI KABUPATEN JEPARA - Arofa, Izanur; Suwarni, Sri; Indrasari, Ferika; Saptawati, Tunik; Gloria, Fransisca (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2020)
The relatively high use of antibiotics poses a threat to the emergence and spread of antibiotic resistance, there are now several findings that antibiotics have been used freely by the public. These antibiotics are purchased to treat symptoms of flu, fever, cough, sore throat, headache and other minor pain symptoms with a duration of use of less than five days. The level of education and knowledge of the community is one of the causes of this. The DAGUSIBU program (get, use, store and dispose) is the most important thing because knowledge is one way to be able to use medicine, store, get, and dispose properly. The purpose of the study was to determine the effect of knowledge with the implementation of the DAGUSIBU program for antibiotic drugs in the community in Jepara Regency from January to March 2020. This type of research is associative research with observational methods. Data were taken prospectively with a quantitative approach from an action research questionnaire. The sample used amounted to 500 respondents. The sampling technique used purposive sampling. Data were processed with chi square and Wilcoxon statistical tests using the SPSS program. The results showed that after the treatment of counseling with video and exposure to speakers and the provision of brochures on the dangers of antibiotic resistance, there was an influence on the level of knowledge with the implementation of the antibiotic drug DAGUSIBU program in Jepara Regency. as evidenced by the p value of 0.00